Evaluación del cumplimiento del Derecho Humano al Agua en la zona 5 del cantón La Joya de los Sachas, provincia de Orellana, año 2024. - Miriam Susana, Vásquez Herrera (2025)
The evaluation of compliance with the Human Rights to Water in the communities: San Jacinto, San Agustín, La Florida, El Oro, Flor del Bosque, Mariscal Sucre, 10 de Marzo, Brisas del Jivino, Valladolid, Riveras del Jivino, Las Palmeras and Getsemaní , from zone 5 of La Joya de los Sachas located in the Orellana canton, it focuses on studying whether the inhabitants of this area have sufficient safe and equitable access to water, according to the dimensions of this right that is recognized worldwide and it is in the Constitution of Ecuador, as a right of access essential for life. The findings of the study show that the intervened communities are small, therefore they present challenges to guarantee this right. These challenges are related to the limited infrastructure, the possible contamination of water sources, the dispersed composition of the homes and the scarcity of financial and technical resources to maintain adequate service. The present evaluation involved to analyze it, through a qualitative approach, the current access to safe water in the 12 communities, zone 5, therefore I conclude in a general way by stating that the human rights to water is being partially guaranteed, in which it recommends carrying out comprehensive and inclusive management, analyzing the possibility of joining efforts between various actors involved in water management to contribute to the sustainable improvement of the living conditions of its inhabitants, guaranteeing the human rights to water and consequently to its general well-being.